Pulmonary Hypertension in Preterm Infants with Bronchopulmonary Dysplasia - Baker, Christopher D. (Mary Ann Liebert, Inc., 2014)
Bronchopulmonary dysplasia (BPD), the chronic lung disease of prematurity, is a significant contributor to perinatal morbidity and mortality. Premature birth disrupts pulmonary vascular growth and initiates a cascade of events that result in impaired gas exchange, abnormal vasoreactivity, and pulmonary vascular remodeling that may ultimately lead to pulmonary hypertension (PH). Even infants who appear to have mild BPD suffer from varying degrees of pulmonary vascular disease (PVD). Although recent studies have enhanced our understanding of the pathobiology of PVD and PH in BPD, much remains unknown with respect to how PH should be properly defined, as well as the most accurate methods for the diagnosis and treatment of PH in infants with BPD. This article will provide neonatologists and primary care providers, as well as pediatric cardiologists and pulmonologists, with a review of the pathophysiology of PH in preterm infants with BPD and a summary of current clinical recommendations for managing PH in this population.